Importance of fish aggregating devices (FADs) as substrates for food organisms of fish - Ibrahim, Sakri; Ambak, Mohd Azmi; Shamsudin, Lokman; Samsudin, Mohd Zaini (Elsevier Science, 1996)
Various hypothesis have been proposed to explain why floating artificial habitats are successful in attracting fishes. Food may be a stimulus for aggregating some species around Fish Aggregating Devices (FADs). This study attempts to discover if sessile marine organisms which readily encrust traditional FADs, are important food organisms for fish. A new group of FADs was installed in a rich fishing ground. Different parts of the FADs were sampled every 2 weeks for identification of encrusted organisms, and ten species were identified. The density of the organisms fluctuated with time of immersion. Plankton collected from the water at the FAD sites was also identified. Stomach contents of 90 fishes caught around these FADs were analyzed and the organisms found in the stomachs were compared with those on the FADs. This study suggests that the attraction of fishes to FADs is due to mechanisms other than feeding on organisms encrusting the FADs.